2019
DOI: 10.48550/arxiv.1903.02354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The motivic Igusa zeta function of a space monomial curve with a plane semigroup

Abstract: In this article, we compute the motivic Igusa zeta function of a space monomial curve that appears as the special fiber of an equisingular family whose generic fiber is a complex plane branch. To this end, we determine the irreducible components of the jet schemes of such a space monomial curve. This approach does not only yield a closed formula for the motivic zeta function, but also allows to determine its poles. We show that, while the family of the jet schemes of the fibers is not flat, the number of poles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In [MVV,Example 4.1], it was shown that the motivic Igusa zeta function of Y 1 has three poles: L 2 , L are poles of Z mon Y 1 ,p 1 (t).…”
Section: The Monodromy Zeta Function Of a Space Monomial Curvementioning
confidence: 99%
See 1 more Smart Citation
“…In [MVV,Example 4.1], it was shown that the motivic Igusa zeta function of Y 1 has three poles: L 2 , L are poles of Z mon Y 1 ,p 1 (t).…”
Section: The Monodromy Zeta Function Of a Space Monomial Curvementioning
confidence: 99%
“…The poles of the motivic zeta function of Y 2 were also computed in [MVV,Example 4.1]: they are given by L 3 , L . Similarly as in the previous example, it is easy to see that they all induce eigenvalues of monodromy associated with Y 2 .…”
Section: The Monodromy Zeta Function Of a Space Monomial Curvementioning
confidence: 99%